(untitled) (Bangladesh Journal of Agricultural Research, 2012)
The study identified agronomic practices, analyzed relative profitability, and resource use efficiency of tuberose cultivation in Bangladesh during January 2010. Primary data were collected from 100 randomly selected farmers from Jessore and Chuadanga districts. The results revealed that the per hectare costs of tuberose cultivation were estimated at Tk. 2,00,761 and Tk. 1,29,283 over full cost and variable cost, respectively. The major share of total cost was for human labour (30%) followed by land use (23%), and fertilizer (17%). The total cost was 26% and 12% higher than its competitive crops banana and papaya, respectively. The yield of tuberose was 4,54,425 sticks per hectare. The gross margin and net return were Tk. 5,52,354 and Tk.4,80,876 per hectare, respectively. This net return was 65% higher than banana and 71% higher than papaya cultivation. The BCRs (benefit cost ratio) were 5.27 and 3.39 over variable cost and full cost basis, respectively. Production function revealed that human labour, seedling and irrigation had positive effect on tuberose cultivation. The lack of scientific knowledge, high yielding variety and efficient transport facility were reported to be major problems in tuberose cultivation. Bangladesh J. Agril. Res. 37(3): 457-464, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12123